Factors Influencing Shopee Users’ Purchase Decisions: An Islamic Economics Perspective - Rachmania Nurul Fitri Amijaya (Faculty of Economics and Management, 2024)
The purpose of this study is to investigate the impact of product reviews and trust on Shopee purchasing behavior from the perspective of Islamic Economics. Data was gathered via surveys and analyzed using data analysis procedures such as the validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, F test, and coefficient of determination. This study makes use of product review factors, trust variables, and purchasing decision variables. The result indicates product review and trust are significant positives to purchasing decisions. The study emphasizes the importance of product evaluations and trust in influencing shopping decisions on Shopee within the context of Islamic Economics. Recognizing the interaction of these elements may help firms, platform operators, and legislators make strategic decisions about how to create a climate conducive to internet trade while adhering to ethical and Islamic standards.